The HLA-DR3,DQ2 heterozygous genotype is associated with an accelerated progression of primary sclerosing cholangitis. - Boberg, K; Spurkland, A; Rocca, G; Egeland, T; Saarinen, S; Mitchell, S; Broomé, U; Chapman, R; Olerup, O; Pares, A; Rosina, F; Schrumpf, E (2001)
BACKGROUND: An improvement of prognostic models in primary sclerosing cholangitis (PSC) is needed. In particular, inclusion of prognostic markers that are independent of the disease stage would be advantageous. We investigated whether HLA class II genes associated with PSC are also related to disease progression. METHODS: The study included 265 PSC patients from five European countries with a median follow-up of 9.1 years. The end-points were death (n = 38) or liver transplantation (n = 52). Thirty patients developed cholangiocarcinoma during follow-up. RESULTS: The DRB1*03,DQA1*0501, DQB1*02 (i.e. DR3,DQ2) heterozygous genotype was associated with an increased risk of death or liver transplantation (hazard ratio = 1.63; 95% confidence interval (CI) = 1.06-2.52). The presence of a DQ6 encoding haplotype (DQB1*0603 or DQB1*0602) in DR3,DQ2 negative individuals was associated with a reduced risk of death or liver transplantation (hazard ratio = 0.57; 95% CI = 0.36-0.88). There was a trend towards an increased risk of developing cholangiocarcinoma among DR4,DQ8 positive patients, but this did not reach significance (odds ratio = 2.27; 95% CI = 0.78-6.62). CONCLUSION: The DR3,DQ2 heterozygous genotype is associated with a more rapid progression of PSC, whereas HLA-DQ6 is associated with a retarded disease progression. It is possible that the DR4,DQ8 haplotype is related to cholangiocarcinoma development.